2008
DOI: 10.1080/00480169.2008.36846
|View full text |Cite
|
Sign up to set email alerts
|

Disease threats to sheep associated with intensification of pastoral farming

Abstract: Sheep farming in New Zealand is based on an outdoor grazing system with various systems of grazing management utilised depending on the type of farm and the time of year. In the current grazing systems, periods of high stocking density, sometimes combined with poor husbandry, contribute to infectious diseases such as abortion and salmonellosis. Intensification such as housing or intensive stocking of ewes for lambing, or feedlot systems, are unlikely to become common in sheep production in New Zealand. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Also, Vasileiou, Gougoulis, et al () have found that the prevalence of subclinical mastitis in high‐yielding breeds was significantly higher than the national average prevalence recorded during a nationwide investigation in Greece. Similar theories have been developed regarding meat‐producing flocks in New Zealand by Ridler ().…”
Section: Animal‐related Predisposing Factorsmentioning
confidence: 65%
“…Also, Vasileiou, Gougoulis, et al () have found that the prevalence of subclinical mastitis in high‐yielding breeds was significantly higher than the national average prevalence recorded during a nationwide investigation in Greece. Similar theories have been developed regarding meat‐producing flocks in New Zealand by Ridler ().…”
Section: Animal‐related Predisposing Factorsmentioning
confidence: 65%
“…Beside humans, such effects are likely to have particularly severe repercussions in managed livestock herbivore species, e.g. ruminants and equines, that often harbour high burdens of GI helminths due to slow development of acquired immunity and high transmission rates within herds 44,45 . Thus far, very few studies have examined the impact of helminth infections on the GI microbiota of herbivorous livestock, with inconsistent findings 40,4648 .…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility of the human host to novel zoonoses from livestock is also increasing, because as the populations of both grow, high density living, for both humans and livestock, are adopted as the only solution to the need for efficient accommodation systems and, in the case of livestock, the need to produce cheap food. This increases the disease transmission risk by virtue of the reduced inter-individual distance [ 7 ] and, where it is associated with more stressful living conditions, depletes the immunocompetence that enables them to deal with the disease challenges [ 6 ]. This is nature’s way of steering animal populations towards more sustainable living.…”
Section: Introductionmentioning
confidence: 99%
“…a particularly high standard of health certification is required for cattle exported to Japan, including 21 d isolation, vaccination for a range of the most serious diseases and negative test responses to assays for a range of other major diseases [ 6 ]. On board, the most important causes of cattle mortality, which is less than that for sheep, are heat stress, trauma and respiratory diseases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%